Complex collaboration champions: university third space professionals working together across borders. (3rd July 2019) - Veles, Natalia; Carter, Margaret-Anne; Boon, Helen
ABSTRACT: In an age of global interconnectedness of people, cultures, technology and professions, within higher education, collaborations between university staff increase in complexity and traverse time and space. Global and local changes and challenges give rise to new and hybrid university professionals – third space professionals – often operating outside their predefined work portfolios on various collaborative projects. Analysing the literature on complex collaborations, the authors discuss three dimensions of collaborative engagements: first, culture in its local, national and global representations; second, integration between professions/occupations; and third, the level of interaction/engagement. Integrating these dimensions into a conceptual model, it is proposed that the university third space serves both as a portal between dimensions and as a vehicle for advancing cross-border collaborations. Third space professionals are likely candidates to assume the role of collaboration champions. Further research and development of the proposed model of university complex collaborations will enhance university workforce development, building staff capabilities and thus increasing organisational collaborative capital.